Control of airflow rate in ACB – HVAC systems using Damper - Krishnan, Ananth (2014)
HVAC systems have gained a lot of popularity over the past few decades. Active Chilled Beams have been incorporated in HVAC systems to result in an increase energy efficiency, cost reduction and reduce building height. ACB in HVAC systems have gained popularity since early 2000’s and there is tremendous scope to implement such an energy efficient technology in buildings. Offices and other public places. In this report, the importance of ACB in HVAC systems will be discussed and Internal Model Control Design is implemented to control ACB pressure in the primary duct. This control is achieved by controlling the damper position. An autoidentification program is implemented in LabView which performs system identification automatically. This increases the engineer’s efficiency by saving time and cost. A comparison between PI and PID controller of IMC designed is discussed in detail in the report.